Effects of SNX9 on the structure and function of primary cilia in autosomal dominant polycystic kidney disease - Shen Ai-wen; Hu Wan-qian; Lin Lu; Yu Sheng-qiang (Linchuang shenzangbing zazhi)
Objective To explore the effect and mechanism of SNX9 on primary cilia in autosomal dominant polycystic kidney disease（ADPKD）and provide theoretical rationales for seeking intervention targets.Methods The localization of SNX9 in cystic lining epithelium cell line（WT9-12）was observed by immunofluorescence.And the differential expression of SNX9 between normal renal tubular epithelial cell line（RCTEC）and WT9-12 was detected by Western blot.The expression of IFT88 was detected by Western blot and the change of cilia length examined by immunofluorescence.Results SNX9 existed in both cytoplasm and membrane of WT9-12 and its expression was lower than that in RCTEC（P<0.05）.When the expression of SNX9 was down-regulated,the expression of IFT88 declined and cilia became shorter（P<0.05）.Meanwhile,after the up-regulation of SNX9 by lentivirus,the expression of IFT88 increased and cilia became longer（P<0.01）.Conclusions In ADPKD,SNX9 exists in both membrane and cytoplasm of cyst epithelium and its expression is lower than that of normal renal tubular epithelial cell.As a result,the morphology and function of primary cilia become compromised.An up-regulation of SNX9 preserves the function of primary cilia and it may become a new target for ADPKD therapy.